DETERMINANTS OF INFLATION IN UZBEKISTAN: AN ECONOMETRIC ANALYSIS OF INCOME AND LABOR MARKET DYNAMICS - Eshboyeva, Madina; Sirojiddin , Saitov (Scientific practical conference, 2026)
This study examines the macroeconomic determinants of inflation in Uzbekistan using an econometric approach. Specifically, the impact of real income and employment level on the Consumer Price Index (CPI) is analyzed based on annual data from 2010 to 2020. A logarithmic regression model is employed to estimate the relationship between variables and interpret elasticities. The results indicate that real income has a statistically significant positive effect on inflation, suggesting that increased purchasing power contributes to higher demand-driven price pressures. In contrast, employment level does not show a statistically significant direct effect on CPI within the selected model. Diagnostic tests confirm the absence of multicollinearity and heteroskedasticity, while the Durbin–Watson statistic suggests potential positive autocorrelation. The findings highlight the importance of demand-side factors in shaping inflation dynamics in Uzbekistan. However, the study also acknowledges limitations related to model simplicity and data scope. The results provide useful insights for policymakers in balancing income growth and price stability.